Total Synthesis and Structural Revision of Incargutines A and B - Kinbara, Atsushi; Yamagishi, Takehiro; Ouchi, Hiroki; Miyaoka, Hiroaki (Synlett, 2013)
We achieved the first total synthesis of (±)-incargutines A and B, which were isolated from the roots of Incarvillea arguta, utilizing In(OTf)3-catalyzed enolization of cyclohexenone derivatives subsequent to an intramolecular Alder–Rickert reaction. At first, we synthesized the proposed structures of incargutines A and B. The spectral data of the synthetic proposed compounds did not correspond to those of the natural products. Then, we synthesized the methyl regioisomers of the proposed structures. Spectral data of these synthetic compounds were identical to those of natural incargutines A and B. Therefore, the structures of incargutines A and B were clearly established to be the methyl regioisomers.
Keywords: total synthesis; incargutine; enols; Alder–Rickert reaction; indium